Crimes, Punishment and Prison’s Weltanschauung - Kron, Leposava; Nikolić, Zlatko; Stevanović, Zoran (Zbornik Instituta za kriminološka i sociološka istraživanja, 2011)
The authors of this article argue that the way a society treats its prisoners can tell you much about its culture. The prison system is in many respects an excellent prism through which to examine a particular culture. References to early prisons can be found in a number of ancient cultures. Several thousand years ago, the Babylonians utilised places of imprisonment or Bit Kili for minor criminals as well as for slaves or foreigners. Classical Greece and Rome sporadically used a private prison or carcer privatus for individuals awaiting trial and executions. Ancient Athens had a prison called desmoterion or "the place of chains". The Old Testament reports the use of imprisonment by Egyptians, Philistines, Assyrians and Israelites. Jerusalem at least had three prisons at the time of Nebuchadnezzar, including Beth ha-keli or "house of detention"; Beth haasourim or "house of chains", and Bor, which was little more than an underground cistern. In 1764 Cesare Beccaria published a brief but celebrated treatise Dei delitti e delle pene ("On Crimes and Punishments"); his work relentlessly protests against torture to obtain confessions, secret accusations, the arbitrary discretionary power of judges, the inconsistency and inequality of sentencing, using personal connections to get a lighter sentence, and the use of capital punishment for serious and even minor offenses. Every prison has its own individuality. The strength of its subcultures depends on the idiosyncrasies of its individuality. Prison subcultures make up the relevant components of the prison world and the prison’s Weltanschauung.